2010
DOI: 10.1007/s00520-010-0940-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of HSV reactivation and pro-inflammatory cytokine levels with the severity of stomatitis after BEAM chemotherapy and autologous SCT

Abstract: We found a significant association between the presence of HSV in saliva samples and severity of stomatitis in patients receiving HD chemotherapy and subsequent autologous SCT. While acyclovir prophylaxis has become standard for patients undergoing allogeneic SCT, this issue has not been sufficiently explored for other chemotherapy regimens. Based on our findings, conduction of a well-powered controlled randomized trial may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…Our findings support the use of antiviral prophylaxis in HSV-seropositive HSCT recipients. 27 A previous study found an association between HSV-1 and stomatitis in autologous HSCT recipients as well, 28 whereas another study failed to establish a relationship between the presence of HSV-1 and mucositis in HSCT recipients. 4 The use of antiviral prophylaxis probably limited the role of HSV in this latter study.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support the use of antiviral prophylaxis in HSV-seropositive HSCT recipients. 27 A previous study found an association between HSV-1 and stomatitis in autologous HSCT recipients as well, 28 whereas another study failed to establish a relationship between the presence of HSV-1 and mucositis in HSCT recipients. 4 The use of antiviral prophylaxis probably limited the role of HSV in this latter study.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, a trend toward increasing levels of proinflammatory cytokines, such as as TNF-a and IL-1, in the first days after autologous and allogeneic HSCT, although some contradictory results in salivary TNF-a levels in UWS and SWS have been reported [15,38,39] (Figure 3; Supplementary Table S3). Little is known about changes in the anti-inflammatory cytokines; only 1 study found increased levels of IL-10 in UWS and SWS of adult allogeneic HSCT recipients at days +7 and +14 [15].…”
Section: Saliva Compositionmentioning
confidence: 99%
“…Rüping et al [172] studied the association of IL-1 and TNF- α in oral saliva and viral pathogens with the severity of ulcerations in autologous HSCT. An association of the severity of oral ulceration and HSV reactivation was demonstrated.…”
Section: Infectionsmentioning
confidence: 99%